Adoption Of E-Commerce In Small And Medium-Sized Enterprises In Bogor District - Nugroho Himawan, Erry; Djuwaini, Ahmad; Darmawan Putra, Awang (Publisher Cv. Inara, 2024)
In recent years, e-commerce has emerged as one of the most rapidly expanding commercial trends. This trend is propelled by the growing prevalence of internet access and the widespread adoption of smartphones in society. Small and medium-sized enterprises (SMEs) play a significant role in the Indonesian economy. The transformation of SMEs must continue to be strengthened through optimizing the use of digital technology so that it can attract benefits for marketing activities and product sales. digital marketing is the most chosen area to start. The challenge is that as many as 30.9% of SMEs still experience difficulties in digital adoption. The objective of this study is to examine the determinants that impact the implementation of electronic commerce by small and medium-sized enterprises in Bogor Regency. This study used an online survey methodology, with a sample size of 170 small and medium-sized enterprises (SMEs) located in Bogor Regency. Data processing was conducted utilizing spreadsheet apps and SmartPLS. The findings indicated that perceived utility, external influences, and attitude towards adopting e-commerce are influential and statistically significant factors in promoting e-commerce adoption. Regarding the perceived ease of use, the attitude towards adopting e-commerce is not influenced by technical readiness and organizational readiness. This research has several implications for small and medium-sized enterprises (SMEs), government entities, and e-commerce administrators. This research demonstrates the imperative for SMEs to enhance their knowledge and skills in utilizing e-commerce, while also enhancing their organizational governance and receptiveness to change, particularly at the top management level. The government requires consistency in offering support to small and medium enterprises (SMEs) in their use of e-commerce, including training, financial aid, and innovation.